Opis przypadkuAutologous pericardium as patch material in the high pressure-system – report of a case of subsequent development of an aneurysm and review of the literature - Kurt, Muhammed; Krian, Arno; Litmathe, Jens (Archives of Medical Science, 2006)
We report the case of a young patient who underwent renewed aortic valve replacement, after open blasting of the aortic valve and subsequent valve replacement with enlargement of the ascending thoracic aorta using an autologous pericardium patch had already taken place. In the context of the former enlargement of the aortic root the development of an aneurysm was seen and was resected in the same setting without any difficulties. Particular items with special regard to the postoperative course, including neurological symptoms due to prolonged operation and cross-clamp-times, are delineated in the following report and compared to the current findings from the literature.